A catalyst component for the polymerization of olefins, process for its preparation, catalyst and use thereof

CN118812747BActive Publication Date: 2026-10-13CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310416420.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-18
Publication Date
2026-10-13
Estimated Expiration
2043-04-18

AI Technical Summary

Benefits of technology

[0023](1)首先本发明的碳酸酯类化合物对环境相对友好,易于操作,其次,当其用作给电子体时可以明显提高现有聚乙烯催化剂的综合性能,在高氢聚合时,该催化剂在具有较高的活性和较高的聚合物粉料堆积密度的同时,具有更好的氢调敏感性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118812747B_ABST
    Figure CN118812747B_ABST
Patent Text Reader

Abstract

The application belongs to the field of olefin polymerization, and discloses a catalyst component for olefin polymerization, a preparation method of the catalyst component, a catalyst and application of the catalyst component. The catalyst component comprises a reaction product of a magnesium-containing liquid component, a carbonate compound, a titanium compound and an optional other electron donor compound. The magnesium-containing liquid component is prepared by the following method: in the presence of an inert solvent, a magnesium-containing compound, an organic epoxy compound and an organic phosphorus compound are reacted to obtain the magnesium-containing liquid component. The magnesium-containing compound is at least one of magnesium dihalide, MgR 1 Cl and Mg(OR 2 )Cl; R 1 and R 2 are each independently selected from substituted or unsubstituted C1-C 10 alkyl, and the carbonate compound comprises at least one of compounds of formula I; R1-R6 are each independently C1-C8 alkyl, C1-C8 halogenated alkyl, H or halogen. The catalyst has higher activity and higher polymer powder bulk density, and better hydrogen sensitivity when high hydrogen polymerization is performed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of olefin polymerization technology, and more specifically, to a catalyst component for olefin polymerization, its preparation method, the catalyst, and its application. Background Technology

[0002] Since its invention in the 1930s, polyethylene has been widely used in industry, agriculture, packaging and daily consumption due to its abundant raw materials and excellent product performance.

[0003] Catalyst research has always played a crucial role in the synthesis and production of polyethylene. Among them, titanium-magnesium catalysts have gained widespread application and continued to be developed due to their high catalytic efficiency and low cost.

[0004] Because it has been discovered that introducing appropriate electron donors into catalysts can improve their catalytic performance, the research and application of electron donor compounds have become increasingly important in catalyst research. More and more related technologies have been developed, such as: CN199610097400.X uses organosilicon compounds with Si-OC bonds as electron donors; CN200410097973.8 uses alkyl benzoates and their derivatives, and dialkyl phthalates and their derivatives with 2-10 carbon atoms as electron donors, specifically such as ethyl benzoate, ethyl bromobenzoate, butyl benzoate, isobutyl benzoate, hexyl benzoate, cyclomethyl benzoate, diisobutyl phthalate, diethyl phthalate, ethyl butyl phthalate, and dibutyl phthalate; CN20051000531 0.3 Using a haloalkanes as internal electron donors, preferably the haloalkanes are selected from one or more of 1,2-dichloroethane, 1,3-dichloropropane, 1,4-dichlorobutane, 1,6-dichlorohexane, monochlorocyclohexane, dichlorocyclohexane, monochlorocyclopentane, and dichlorocyclopentane; CN201510531912.6 When organic acid anhydrides / acetic acid esters / aromatic esters are introduced as complex electron donors into the N-type polyolefin catalyst preparation system, spherical / ellipsoidal magnesium / titanium-containing solid particles can be prepared; CN201911060404.9 Diphenylanthracene derivatives are used as internal electron donor compounds.

[0005] With the development of the polyolefin industry, there is a need to continuously develop more and better electron donors to meet the industry's higher requirements for catalysts. Summary of the Invention

[0006] The purpose of this invention is to provide a catalyst component for olefin polymerization, its preparation method, catalyst, and application. This invention uses a specific carbonate compound as an electron donor to prepare the catalyst component, thereby enabling the prepared catalyst to have better overall performance. In high-hydrogen polymerization, this catalyst has higher activity and higher polymer powder packing density, while also exhibiting better hydrogen regulation sensitivity.

[0007] To achieve the above objectives, a first aspect of the present invention provides a catalyst component for olefin polymerization, the catalyst component comprising a magnesium-containing liquid component, a carbonate compound, a titanium compound, and optionally other electron-donating compounds as reaction products.

[0008] The magnesium-containing liquid component is prepared by reacting a magnesium-containing compound, an organic epoxy compound, and an organic phosphorus compound in the presence of an inert solvent to obtain the magnesium-containing liquid component.

[0009] The magnesium-containing compound is magnesium dihalide or MgR. 1 Cl and Mg(OR) 2 At least one of Cl; R 1 and R 2 Each is independently selected from substituted or unsubstituted C1-C 10 The hydrocarbon group, wherein the substituent is selected from at least one of hydroxyl, carboxyl, halogen atom and alkoxy group;

[0010] The carbonate compounds comprise at least one of the compounds shown in Formula I; wherein R1-R6 are each independently a C1-C8 hydrocarbon group, a C1-C8 halohydrocarbon group, H, or a halogen;

[0011]

[0012] A second aspect of the present invention provides a method for preparing the above-mentioned catalyst component, the method comprising:

[0013] (1) The magnesium-containing compound, the organic epoxy compound and the organic phosphorus compound are reacted in the presence of an inert solvent to obtain the magnesium-containing liquid component;

[0014] (2) The magnesium-containing liquid component obtained in step (1), carbonate compounds, titanium compounds and optional other electron-donating compounds are reacted to produce precipitates;

[0015] (3) Remove unreacted substances and solvents, wash the precipitate, and obtain the catalyst component.

[0016] A third aspect of the present invention provides a catalyst for olefin polymerization, the catalyst comprising the following components:

[0017] Component A: The catalyst components mentioned above;

[0018] Component B: Organoaluminum compound; its general formula is AlR n X 3-n In the formula, R is a hydrocarbon group with 1 to 20 carbon atoms; X is a halogen, preferably chlorine or bromine; n is an integer 0 < n ≤ 3;

[0019] Preferably, the molar ratio of aluminum in component B to titanium in component A is 1 to 1000:1, more preferably 5 to 500:1;

[0020] The organoaluminum compound is preferably at least one of trimethylaluminum, triethylaluminum, triisobutylaluminum, trioctylaluminum, diethylaluminum hydrogen, diisobutylaluminum hydrogen, diethylaluminum chloride, diisobutylaluminum chloride, sesquiethylaluminum chloride, and diethylaluminum chloride; more preferably triethylaluminum and / or triisobutylaluminum.

[0021] A fourth aspect of the present invention provides the use of the above-described catalyst component or the above-described catalyst in olefin polymerization reactions.

[0022] Compared with existing technologies, the present invention has the following obvious advantages:

[0023] (1) Firstly, the carbonate compounds of the present invention are relatively environmentally friendly and easy to operate. Secondly, when used as electron donors, they can significantly improve the overall performance of existing polyethylene catalysts. In high-hydrogen polymerization, the catalyst has higher activity and higher polymer powder packing density, while also having better hydrogen regulation sensitivity.

[0024] (2) The raw materials used in the catalyst of the present invention are relatively environmentally friendly, and the catalyst preparation process is simple.

[0025] Other features and advantages of the present invention will be described in detail in the following detailed description section. Detailed Implementation

[0026] Preferred embodiments of the invention will now be described in more detail. While preferred embodiments of the invention are described below, it should be understood that the invention can be implemented in various forms and should not be limited to the embodiments set forth herein.

[0027] A first aspect of the present invention provides a catalyst composition for olefin polymerization, the catalyst composition comprising a magnesium-containing liquid component, a carbonate compound, a titanium compound, and optionally other electron-donating compounds as reaction products.

[0028] The magnesium-containing liquid component is prepared by reacting a magnesium-containing compound, an organic epoxy compound, and an organic phosphorus compound in the presence of an inert solvent to obtain the magnesium-containing liquid component.

[0029] The magnesium-containing compound is magnesium dihalide or MgR. 1 Cl and Mg(OR) 2 At least one of Cl; R 1 and R 2 Each is independently selected from substituted or unsubstituted C1-C 10 The hydrocarbon group, wherein the substituent is selected from at least one of hydroxyl, carboxyl, halogen atom and alkoxy group;

[0030] The carbonate compounds comprise at least one of the compounds shown in Formula I; wherein R1-R6 are each independently a C1-C8 hydrocarbon group, a C1-C8 halohydrocarbon group, H, or a halogen;

[0031]

[0032] In this invention, the inventors, through extensive experimental research during the development of polyethylene catalysts, surprisingly discovered that specific carbonate compounds, as shown in Formula I, can significantly improve the overall performance of specific titanium-magnesium polyolefin catalysts when used as electron donors, especially demonstrating a marked improvement in the hydrogen sensitivity of the catalyst during high-hydrogen polymerization. Based on this discovery, this invention provides a catalyst component for olefin homopolymerization or copolymerization.

[0033] In this invention, the C1-C in the general formula of the aforementioned magnesium-containing compounds 10 The hydrocarbon group can be alkyl, cycloalkyl, alkenyl, alkynyl, aryl, or aralkyl, etc. Specifically:

[0034] C1-C 10 Alkyl refers to C1-C 10 Straight-chain alkyl or C3-C 10 Branched alkyl groups, non-limiting examples of which include: methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, tert-pentyl, neopentyl, n-hexyl, n-heptyl, n-octyl, and n-decyl.

[0035] C3-C 10 Examples of cycloalkyl groups may include, but are not limited to: cyclopropyl, cyclopentyl, cyclohexyl, 4-methylcyclohexyl, 4-ethylcyclohexyl, 4-n-propylcyclohexyl, and 4-n-butylcyclohexyl.

[0036] C6-C 10 Examples of aryl groups may include, but are not limited to, phenyl, 4-methylphenyl, and 4-ethylphenyl.

[0037] C2-C 10 Examples of alkenyl groups may include, but are not limited to, vinyl and allyl groups.

[0038] C7-C 10 Examples of aralkyl groups may include, but are not limited to: phenylmethyl, phenylethyl, phenyl-n-propyl, phenyl-n-butyl, phenyl-tert-butyl, and phenylisopropyl.

[0039] In this invention, the "substituted C1-C" in the general formula of the aforementioned magnesium-containing compounds 10 "hydrocarbon group" refers to "C1-C 10 The hydrogen atom (preferably one hydrogen atom) and / or carbon atom on the hydrocarbon group are replaced by the substituents.

[0040] In the preferred case, R 1 and R 2 Selected from substituted or unsubstituted C1-C 10 Alkyl groups.

[0041] According to the present invention, preferably, the magnesium dihalide is at least one of magnesium dichloride, magnesium dibromide and magnesium diiodide, and more preferably magnesium dichloride;

[0042] The MgR 1 Cl is CH3MgCl and / or CH3CH2MgCl;

[0043] The Mg(OR) 2 Cl is MgCl(OCH2CH3) and / or MgCl(OBu).

[0044] According to the present invention, preferably, the organophosphorus compound is selected from at least one of trimethyl phosphate, triethyl phosphate, tri-n-propyl phosphate, triisopropyl phosphate, tri-n-butyl phosphate, triisobutyl phosphate, tri-tert-butyl phosphate, tri-n-pentyl phosphate, triisopentyl phosphate, tri-n-hexyl phosphate, triisohexyl phosphate, tri-n-heptyl phosphate, triisoheptyl phosphate, tri-n-octyl phosphate, triisooctyl phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, tri-n-propyl phosphite, triisopropyl phosphite, tri-n-butyl phosphite, triisobutyl phosphite, tri-tert-butyl phosphite, tri-n-pentyl phosphite, triisopentyl phosphite, tri-n-hexyl phosphite, triisoheptyl phosphite, tri-n-octyl phosphite, triisooctyl phosphite, triphenyl phosphite, and di-n-butyl phosphite.

[0045] The organophosphorus compound is preferably at least one selected from triethyl phosphate, tributyl phosphate, triisooctyl phosphate, triphenyl phosphate, triethyl phosphite, tributyl phosphite, and di-n-butyl phosphite.

[0046] According to the present invention, preferably, the organic epoxy compound is selected from at least one of oxides of C2-C8 aliphatic olefins, glycidyl ethers of C2-C8 aliphatic olefins, internal ethers of C2-C8 aliphatic olefins, oxides of C2-C8 halogenated aliphatic olefins, glycidyl ethers of C2-C8 halogenated aliphatic olefins, and internal ethers of C2-C8 halogenated aliphatic olefins; preferably at least one of ethylene oxide, propylene oxide, butane oxide, butane dioxide, epichlorohydrin, methyl glycidyl ether, diglycidyl ether, and tetrahydrofuran; more preferably at least one of ethylene oxide, propylene oxide, epichlorohydrin, and tetrahydrofuran.

[0047] According to the present invention, preferably, the carbonate compound includes at least one of the following: iodomethyl isopropyl carbonate, methyl carbonate, dimethyl carbonate, di(trichloromethyl) carbonate, dimethyl chlorocarbonate, ethyl methyl carbonate, diethyl carbonate, diisopropyl carbonate, 1-chloroethylethyl carbonate, isopropyl chloromethyl carbonate, and 1-chloroethyl isopropyl carbonate; preferably at least one of the following halogenated carbonates; more preferably di(trichloromethyl) carbonate.

[0048] According to the present invention, preferably, the titanium compound has the general formula TiX. n (OR) 4-n Where: X is a halogen, and R is a C1 to C2 halogen. 14 aliphatic hydrocarbon groups or C6~C 14 Aromatic hydrocarbon groups, where n is an integer from 0 to 4;

[0049] The titanium compound is preferably at least one of titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, titanium tetraethoxy, titanium tetrabutoxy, titanium monochlorotriethoxy, titanium dichlorodiethoxy, and titanium trichloromonethoxy; more preferably at least one of titanium tetrachloride, titanium tetraethoxy, and titanium tetrabutoxy.

[0050] According to the present invention, preferably, the other electron-donating compound is selected from at least one of organic acid anhydrides, organic acids, organic acid esters, organic acyl halides, ethers, ketones, amines, phosphate esters, amides, phenols, pyridines, and organic alcohols; the organic alcohols include C1-C1 compounds. 12 fatty alcohols, C7-C 12 At least one of aromatic alcohols and substituted alcohols, wherein the substituted alcohol is C1 to C2. 12 fatty alcohols and / or C7-C6 12 Substituted alcohols derived from aromatic alcohols;

[0051] The other electron-donating compounds are preferably acetic anhydride, phthalic anhydride, succinic anhydride, maleic anhydride, acetic acid, propionic acid, butyric acid, acrylic acid, methacrylic acid, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl benzoate, ethyl benzoate, butyl benzoate, ethyl p-methylbenzoate, di-n-butyl phthalate, diisobutyl phthalate, diethyl succinate, dipropyl succinate, diisopropyl succinate, methyl naphthol, ethyl naphthol, methyl methyl benzoate, acyl chloride, diethyl ether, and butyl ether. The alcohol is at least one of the following: tetrahydrofuran, acetone, butanone, cyclohexanone, phenol, methanol, ethanol, propanol, butanol, 2-methylpentanol, 2-ethylbutanol, n-heptanol, n-octanol, 2-ethylhexanol, n-decanol, dodecanol, cyclohexanol, methylcyclohexanol, benzyl alcohol, and haloalcohol; wherein the haloalcohol is a haloalcohol derived from at least one of methanol, ethanol, propanol, butanol, 2-methylpentanol, 2-ethylbutanol, n-heptanol, n-octanol, 2-ethylhexanol, n-decanol, dodecanol, cyclohexanol, methylcyclohexanol, and benzyl alcohol.

[0052] According to the present invention, preferably, the inert solvent is a liquid hydrocarbon, which preferably includes at least one of halogenated aromatic hydrocarbons, non-halogenated aromatic hydrocarbons, halogenated aliphatic hydrocarbons, and non-halogenated aliphatic hydrocarbons; more preferably, at least one of benzene and its homologues, chlorobenzene, dichlorobenzene, hexane, heptane, decane, kerosene, dichloromethane, dichloroethane, chloroform, and cyclohexane.

[0053] According to the present invention, preferably, per mole of magnesium-containing compound, the organophosphorus compound is 0.01 to 10 moles, more preferably 0.1 to 4 moles; the organic epoxy compound is 0.01 to 10 moles, more preferably 0.1 to 4 moles; the carbonate compound is 0.001 to 10 moles, more preferably 0.002 to 1 mole; the other electron-donating compounds are 0 to 10 moles, more preferably 0 to 4 moles; and the titanium compound is 0.2 to 100 moles, more preferably 1.0 to 20 moles.

[0054] A second aspect of the present invention provides a method for preparing the above-mentioned catalyst component, the method comprising:

[0055] (1) The magnesium-containing compound, the organic epoxy compound and the organic phosphorus compound are reacted in the presence of an inert solvent to obtain the magnesium-containing liquid component;

[0056] (2) The magnesium-containing liquid component obtained in step (1), carbonate compounds, titanium compounds and optional other electron-donating compounds are reacted to produce precipitates;

[0057] (3) Remove unreacted substances and solvents, wash the precipitate, and obtain the catalyst component.

[0058] In this invention, the magnesium-containing liquid component is a homogeneous solution.

[0059] In this invention, preferably, in step (1), the reaction temperature is 40-80°C and the time is 0.1-10 hours.

[0060] In this invention, preferably, step (2) involves adding other electron-donating compounds to the magnesium-containing liquid component obtained in step (1) for reaction, then reacting it with the carbonate compound, and finally reacting it with the titanium compound to produce a precipitate.

[0061] The above preparation method is an example description of catalyst component A of the present invention. In actual feeding, the specific carbonate compound of the present invention can also be added after the titanium compound. In addition, the above components are only the basic components of the present invention. In actual synthesis, it is not limited to these basic components. If necessary, other electron donors and additives can also be added at the same time. The present invention will not point them out one by one here.

[0062] More specifically, the catalyst component of the present invention can be prepared by the following method: Magnesium halide is reacted with an organophosphorus compound and an organic epoxy compound at a temperature of 40–80°C under stirring and in the presence of an inert solvent to form a homogeneous and transparent solution. Optionally, other electron-donating compounds are added, along with carbonate compounds. At a temperature of -35–60°C, preferably -30–30°C, a titanium compound is added dropwise to the mixture, or the mixture is added dropwise to the titanium compound. After the addition is complete, the temperature can be maintained for a period of time. Optionally, other electron-donating compounds can be added again. Then, the temperature is increased, preferably at a rate of 4–200°C per hour. The reaction mixture is then stirred at a temperature of 30–150°C, preferably 50–130°C, for 1 minute to 10 hours. Stirring is stopped, the mixture is allowed to settle, filtered, and the mother liquor is removed. The solid is washed with hydrocarbon solvents such as toluene and hexane to obtain a titanium-containing solid catalyst component.

[0063] After the above steps, component A of the catalyst of the present invention is obtained, which can be used in the form of a solid or a suspension.

[0064] A third aspect of the present invention provides a catalyst for olefin polymerization, the catalyst comprising the following components:

[0065] Component A: The catalyst components mentioned above;

[0066] Component B: Organoaluminum compound; its general formula is AlR n X 3-n In the formula, R is a hydrocarbon group with 1 to 20 carbon atoms; X is a halogen, preferably chlorine or bromine; n is an integer 0 < n ≤ 3;

[0067] Preferably, the molar ratio of aluminum in component B to titanium in component A is 1 to 1000:1, more preferably 5 to 500:1;

[0068] The organoaluminum compound is preferably at least one of trimethylaluminum, triethylaluminum, triisobutylaluminum, trioctylaluminum, diethylaluminum hydrogen, diisobutylaluminum hydrogen, diethylaluminum chloride, diisobutylaluminum chloride, sesquiethylaluminum chloride, and diethylaluminum chloride; more preferably triethylaluminum and / or triisobutylaluminum.

[0069] In this invention, R is a hydrocarbon group having 1 to 20 carbon atoms, wherein the hydrocarbon group can be alkyl, aralkyl, aryl, etc.

[0070] In this invention, trimethylaluminum, triethylaluminum, triisobutylaluminum, and trioctylaluminum belong to trialkylaluminum; diethylaluminum monohydrogen and diisobutylaluminum monohydrogen belong to alkylaluminum hydrogenates; and diethylaluminum monochloro, diisobutylaluminum monochloro, sesquiethylaluminum chloride, and diethylaluminum dichlorochloride belong to alkylaluminum chlorides.

[0071] The A and B components (organoaluminum compounds) of the catalyst of this invention can be directly applied to the polymerization system, or they can be pre-complexed and then applied to the polymerization system.

[0072] A fourth aspect of the present invention provides the use of the above-described catalyst component or the above-described catalyst in olefin polymerization reactions.

[0073] The catalyst component or catalyst of the present invention can be used for homopolymerization of ethylene, and can also be used for copolymerization of ethylene and α-olefins. The comonomer can be propylene, butene, pentene, hexene, octene, or 4-methyl-1-pentene.

[0074] Polymerization can be performed in either the liquid phase or the gas phase. In liquid phase polymerization, inert solvents such as propane, hexane, heptane, cyclohexane, isobutane, isopentane, naphtha, raffinate, hydrogenated gasoline, kerosene, benzene, toluene, and xylene, or saturated aliphatic or aromatic hydrocarbons, can be used as the reaction medium. Prepolymerization can be performed before polymerization. Polymerization can be carried out in batch, semi-continuous, or continuous processes.

[0075] The polymerization temperature is room temperature to 150°C, preferably 50°C to 100°C. Hydrogen is used as a molecular weight regulator to adjust the polymer's molecular weight.

[0076] The following embodiments are examples of the present invention in more detail, but the present invention is not limited to these embodiments.

[0077] In the following examples and comparative examples:

[0078] Determination of polymer melt index (MI): According to ASTM D1238-99, the test was conducted at 190°C with a load of 2.16 kg.

[0079] Polymer bulk density was determined using the test method for apparent density, volume factor and pourability of plastics (ASTM D1895).

[0080] (I) Catalyst Components Preparation

[0081] Example 1

[0082] Preparation of solid catalyst component a

[0083] 4.0 g of anhydrous magnesium chloride, 90 mL of toluene, 8.0 mL of epichlorohydrin, and 16.0 mL of tri-n-butyl phosphate were sequentially added to a reactor that had undergone repeated purging with high-purity nitrogen. The reaction was carried out at 60 °C for 2 hours. Then, 2.0 g of phthalic anhydride was added, and the mixture was kept at this temperature for 1 hour. The system was then cooled to 30 °C, and 3.0 mL of dimethyl carbonate was slowly added dropwise, maintaining this temperature for 0.5 hours. The system was then cooled to -35 °C, and 70 mL of titanium tetrachloride was added. The temperature was gradually increased to 110 °C and kept at this temperature for 2 hours. Stirring was stopped, the mixture was allowed to stand, and the supernatant was removed. After washing with toluene and hexane multiple times, the mixture was dried to obtain solid catalyst component a.

[0084] Comparative Example 1

[0085] Preparation of solid catalyst component a*

[0086] 4.0 g of anhydrous magnesium chloride, 90 mL of toluene, 8.0 mL of epichlorohydrin, and 16.0 mL of tri-n-butyl phosphate were sequentially added to a reactor that had undergone repeated purging with high-purity nitrogen. The reaction was carried out at 60 °C for 2 hours. Then, 2.0 g of phthalic anhydride was added, and the mixture was kept at this temperature for 1 hour. The system was then cooled to 30 °C and maintained for 0.5 hours. Finally, the system was cooled to -35 °C, and 70 mL of titanium tetrachloride was added. The temperature was gradually increased to 110 °C and kept at this temperature for 2 hours. Stirring was stopped, the mixture was allowed to stand, and the supernatant was removed. After washing with toluene and hexane multiple times, the mixture was dried to obtain solid catalyst component a*.

[0087] Example 2

[0088] Preparation of solid catalyst component b

[0089] 4.0 g of anhydrous magnesium chloride, 90 mL of toluene, 8.0 mL of epichlorohydrin, and 16.0 mL of tri-n-butyl phosphate were sequentially added to a reactor that had undergone repeated purging with high-purity nitrogen. The reaction was carried out at 60 °C for 2 hours. Then, 2.0 g of phthalic anhydride was added, and the mixture was kept at this temperature for 1 hour. The system was then cooled to 30 °C, and 3.0 mL of diethyl carbonate was slowly added dropwise, maintaining this temperature for 0.5 hours. The system was then cooled to -35 °C, and 70 mL of titanium tetrachloride was added. The temperature was gradually increased to 110 °C and kept at this temperature for 2 hours. Stirring was stopped, the mixture was allowed to stand, and the supernatant was removed. After washing with toluene and hexane multiple times, the mixture was dried to obtain solid catalyst component b.

[0090] Comparative Example 2

[0091] Preparation of solid catalyst component b*

[0092] 4.0 g of anhydrous magnesium chloride, 90 mL of toluene, 8.0 mL of epichlorohydrin, and 16.0 mL of tri-n-butyl phosphate were sequentially added to a reactor that had undergone repeated purging with high-purity nitrogen. The reaction was carried out at 60 °C for 2 hours. Then, 2.0 g of phthalic anhydride was added, and the mixture was kept at this temperature for 1 hour. The system was then cooled to 30 °C, and 3.0 mL of ethyl benzoate was slowly added dropwise, maintaining this temperature for 0.5 hours. The system was then cooled to -35 °C, and 70 mL of titanium tetrachloride was added. The temperature was gradually increased to 110 °C and kept at this temperature for 2 hours. Stirring was stopped, the mixture was allowed to stand, and the supernatant was removed. After washing with toluene and hexane multiple times, the mixture was dried to obtain the solid catalyst component b*.

[0093] Example 3

[0094] Preparation of solid catalyst component c

[0095] 4.0 g of anhydrous magnesium chloride, 90 mL of toluene, 6.0 mL of epichlorohydrin, and 12.0 mL of triisobutyl phosphate were sequentially added to a reactor that had undergone repeated purging with high-purity nitrogen. The reaction was carried out at 60 °C for 2 hours. The system was then cooled to 30 °C, and 3.0 g of bis(trichloromethyl) carbonate was added. The temperature was maintained for 0.5 hours, and the system was then cooled to -35 °C. Subsequently, 70 mL of titanium tetrachloride was added, and the temperature was gradually increased to 90 °C and maintained for 2 hours. Stirring was stopped, the mixture was allowed to stand, and the supernatant was removed. After washing with toluene and hexane multiple times, the mixture was dried to obtain solid catalyst component c.

[0096] Comparative Example 3

[0097] Preparation of solid catalyst component c

[0098] 4.0 g of anhydrous magnesium chloride, 90 mL of toluene, 6.0 mL of epichlorohydrin, and 12.0 mL of triisobutyl phosphate were sequentially added to a reactor that had undergone repeated purging with high-purity nitrogen. The reaction was carried out at 60 °C for 2 hours. The system was then cooled to 30 °C and maintained for 0.5 hours, followed by cooling to -35 °C. Subsequently, 70 mL of titanium tetrachloride was added, and the temperature was gradually increased to 90 °C and maintained for 2 hours. Stirring was stopped, the mixture was allowed to stand, and the supernatant was removed. After washing with toluene and hexane multiple times, the mixture was dried to obtain the solid catalyst component c*.

[0099] Example 4

[0100] Preparation of solid catalyst component d

[0101] In a reactor that has undergone repeated purging with high-purity nitrogen, 4.0 g of anhydrous magnesium chloride, 70 mL of toluene, 4 mL of epichlorohydrin, and 12 mL of tri-n-butyl phosphate were added sequentially. The reaction was carried out at 60 °C for 1 hour. Then, 0.5 g of di(trichloromethyl) carbonate was added and the reaction was maintained for 0.5 hours. The temperature was then lowered to -30 °C, and 60 mL of titanium tetrachloride was added dropwise. The reaction was maintained for 1 hour, and then 2.0 mL of ethyl benzoate was added dropwise. The reaction was maintained for 1 hour, and the temperature was gradually raised to 110 °C and held at 110 °C for 1 hour. The stirring was then stopped, the mixture was allowed to stand, and the supernatant was removed. After washing with hexane multiple times, the mixture was dried to obtain solid catalyst component d.

[0102] Comparative Example 4

[0103] Preparation of solid catalyst component d*

[0104] In a reactor that has undergone repeated purging with high-purity nitrogen, 4.0 g of anhydrous magnesium chloride, 70 mL of toluene, 4 mL of epichlorohydrin, and 12 mL of tri-n-butyl phosphate were added sequentially. The reaction was carried out at 60 °C for 1.5 hours, then cooled to -30 °C. 60 mL of titanium tetrachloride was added dropwise and maintained for 1 hour. 2.0 mL of ethyl benzoate was added dropwise and maintained for 1 hour. The temperature was gradually raised to 110 °C and held at 110 °C for 1 hour. Stirring was stopped, the mixture was allowed to stand, the supernatant was removed, and the mixture was washed multiple times with hexane and dried to obtain the solid catalyst component d*.

[0105] Example 5

[0106] Preparation of solid catalyst component e

[0107] In a reactor that has undergone repeated purging with high-purity nitrogen, 4.0 g of anhydrous magnesium chloride, 70 mL of toluene, 4 mL of epichlorohydrin, and 12 mL of tri-n-butyl phosphate were added sequentially. The reaction was carried out at 60 °C for 1 hour. Then, 2.0 g of di(trichloromethyl) carbonate was added and the reaction was maintained for 0.5 hours. The temperature was then lowered to -30 °C, and 40 mL of titanium tetrachloride was added dropwise. The reaction was maintained for 1 hour, and the temperature was gradually raised to 110 °C. The temperature was then maintained at 110 °C for 1 hour. The stirring was stopped, the mixture was allowed to stand, and the supernatant was removed. After washing with hexane multiple times, the mixture was dried to obtain solid catalyst component e.

[0108] Comparative Example 5

[0109] Preparation of solid catalyst component e*

[0110] In a reactor that has undergone repeated purging with high-purity nitrogen, 4.0 g of anhydrous magnesium chloride, 70 mL of toluene, 4 mL of epichlorohydrin, and 12 mL of tri-n-butyl phosphate were added sequentially. The reaction was carried out at 60 °C for 1 hour. Then, 1.0 mL of ethyl benzoate was added and the reaction was maintained for 0.5 hours. The temperature was then lowered to -30 °C, and 40 mL of titanium tetrachloride was added dropwise. The reaction was maintained for 1 hour, and the temperature was gradually raised to 110 °C. The temperature was then maintained at 110 °C for 1 hour. The stirring was stopped, the mixture was allowed to stand, and the supernatant was removed. After washing with hexane multiple times, the mixture was dried to obtain the solid catalyst component e*.

[0111] Example 6

[0112] Preparation of solid catalyst component f

[0113] In a reactor that has undergone repeated purging with high-purity nitrogen, 4.0 g of anhydrous magnesium chloride, 70 mL of toluene, 4 mL of epichlorohydrin, and 12 mL of tri-n-butyl phosphate were added sequentially. The reaction was carried out at 60 °C for 1 hour. Then, 1.0 g of bis(trichloromethyl) carbonate was added and the reaction was maintained for 0.5 hours. The temperature was then lowered to -30 °C, and 90 mL of titanium tetrachloride was added dropwise. The reaction was maintained for 1 hour, and the temperature was gradually raised to 70 °C. The temperature was then maintained at 70 °C for 3 hours. The stirring was stopped, the mixture was allowed to stand, and the supernatant was removed. After washing with hexane multiple times, the mixture was dried to obtain solid catalyst component f.

[0114] Comparative Example 6

[0115] Preparation of solid catalyst component f*

[0116] The rest is the same as in Example 6, except that 1.0 g of bis(trichloromethyl) carbonate is replaced with 0.7 ml of tetraethoxysilane.

[0117] (II) Ethylene Polymerization

[0118] A 2-liter stainless steel reactor was fully purged with H2, then 1000 mL of hexane, 1.0 mL of a 1 mol / L triethylaluminum hexane solution, and a measured amount (containing approximately 0.04 mmol of titanium) of the prepared solid catalyst were added. The reactor was heated to 70°C and hydrogen was added at 0.58 MPa (gauge pressure). Ethylene was then introduced to bring the pressure inside the reactor to 0.73 MPa (gauge pressure), and polymerization was carried out at 85°C for 2 hours. The experimental results are shown in the table below:

[0119] Table 1. Experimental Results

[0120]

[0121]

[0122] As can be seen from the data in the table above, the addition of specific carbonate compounds in this invention can significantly increase the melt index (MI) of the corresponding polymers. 2.16 ).

[0123] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A catalyst component for olefin polymerization, characterized in that, The catalyst composition comprises a magnesium-containing liquid component, carbonate compounds, titanium compounds, and optional other electron-donating compounds as reaction products. The magnesium-containing liquid component is prepared by reacting a magnesium-containing compound, an organic epoxy compound, and an organic phosphorus compound in the presence of an inert solvent to obtain the magnesium-containing liquid component. The magnesium-containing compound is magnesium dihalide or MgR. 1 Cl and Mg (OR) 2 At least one of Cl; R 1 and R 2 Each is independently selected from substituted or unsubstituted C1-C 10 The hydrocarbon group, wherein the substituent is selected from at least one of hydroxyl, carboxyl, halogen atom and alkoxy group; The carbonate compound is bis(trichloromethyl) carbonate.

2. The catalyst component according to claim 1, wherein, The magnesium dihalide is at least one of magnesium dichloride, magnesium dibromide, and magnesium diiodide; The MgR 1 Cl is CH3MgCl and / or CH3CH2MgCl; The Mg(OR) 2 Cl is MgCl(OCH2CH3) and / or MgCl(OBu).

3. The catalyst component according to claim 1, wherein, The magnesium dihalide mentioned is magnesium dichloride.

4. The catalyst component according to claim 1, wherein, The organophosphorus compound is selected from at least one of trimethyl phosphate, triethyl phosphate, tri-n-propyl phosphate, triisopropyl phosphate, tri-n-butyl phosphate, triisobutyl phosphate, tri-tert-butyl phosphate, tri-n-pentyl phosphate, triisopentyl phosphate, tri-n-hexyl phosphate, triisohexyl phosphate, tri-n-heptyl phosphate, triisoheptyl phosphate, tri-n-octyl phosphate, triisooctyl phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, tri-n-propyl phosphite, triisopropyl phosphite, tri-n-butyl phosphite, triisobutyl phosphite, tri-tert-butyl phosphite, tri-n-pentyl phosphite, triisopentyl phosphite, tri-n-hexyl phosphite, triisohexyl phosphite, tri-n-heptyl phosphite, triisoheptyl phosphite, tri-n-octyl phosphite, triisooctyl phosphite, triphenyl phosphite, and di-n-butyl phosphite.

5. The catalyst component according to claim 4, wherein, The organophosphorus compound is at least one selected from triethyl phosphate, tributyl phosphate, triisooctyl phosphate, triphenyl phosphate, triethyl phosphite, tributyl phosphite, and di-n-butyl phosphite.

6. The catalyst component according to claim 1, wherein, The organic epoxy compound is selected from at least one of the following: oxides of C2-C8 aliphatic olefins, glycidyl ethers of C2-C8 aliphatic olefins, internal ethers of C2-C8 aliphatic olefins, oxides of C2-C8 halogenated aliphatic olefins, glycidyl ethers of C2-C8 halogenated aliphatic olefins, and internal ethers of C2-C8 halogenated aliphatic olefins.

7. The catalyst component according to claim 6, wherein, The organic epoxy compound is at least one selected from ethylene oxide, propylene oxide, butane oxide, butadiene oxide, butadiene dioxide, epichlorohydrin, methyl glycidyl ether, diglycidyl ether, and tetrahydrofuran.

8. The catalyst component according to claim 7, wherein, The organic epoxy compound is at least one of ethylene oxide, propylene oxide, epichlorohydrin, and tetrahydrofuran.

9. The catalyst component according to claim 1, wherein, The general formula of the titanium compound is TiX. n (OR) 4-n Where: X is a halogen, and R is a C1 to C2 halogen. 14 aliphatic hydrocarbon groups or C6~C 14 Aromatic hydrocarbon group, where n is an integer from 0 to 4.

10. The catalyst component according to claim 9, wherein, The titanium compound is at least one selected from titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, titanium tetraethoxy, titanium tetrabutoxy, titanium monochlorotriethoxy, titanium dichlorodiethoxy, and titanium trichloromonoethoxy.

11. The catalyst component according to claim 10, wherein, The titanium compound is at least one of titanium tetrachloride, titanium tetraethoxy, and titanium tetrabutoxy.

12. The catalyst component according to claim 1, wherein, The other electron-donating compounds are selected from at least one of organic acid anhydrides, organic acids, organic acid esters, organic acyl halides, ethers, ketones, amines, phosphate esters, amides, phenols, pyridines, and organic alcohols; the organic alcohols include C1-C1 compounds. 12 fatty alcohols, C7-C 12 At least one of aromatic alcohols and substituted alcohols, wherein the substituted alcohol is C1 to C2. 12 fatty alcohols and / or C7-C6 12 Substituted alcohols derived from aromatic alcohols.

13. The catalyst component according to claim 12, wherein, The other electron-donating compounds are acetic anhydride, phthalic anhydride, succinic anhydride, maleic anhydride, acetic acid, propionic acid, butyric acid, acrylic acid, methacrylic acid, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl benzoate, ethyl benzoate, butyl benzoate, ethyl p-methylbenzoate, di-n-butyl phthalate, diisobutyl phthalate, diethyl succinate, dipropyl succinate, diisopropyl succinate, methyl naphthol, ethyl naphthol, methyl methyl benzoate, acyl chloride, diethyl ether, and butyl ether. The alcohol is at least one selected from tetrahydrofuran, acetone, butanone, cyclohexanone, phenol, methanol, ethanol, propanol, butanol, 2-methylpentanol, 2-ethylbutanol, n-heptanol, n-octanol, 2-ethylhexanol, n-decanol, dodecanol, cyclohexanol, methylcyclohexanol, benzyl alcohol, and haloalcohol; wherein the haloalcohol is a haloalcohol derived from at least one selected from methanol, ethanol, propanol, butanol, 2-methylpentanol, 2-ethylbutanol, n-heptanol, n-octanol, 2-ethylhexanol, n-decanol, dodecanol, cyclohexanol, methylcyclohexanol, and benzyl alcohol.

14. The catalyst component according to claim 1, wherein, The inert solvent is a liquid hydrocarbon.

15. The catalyst component according to claim 14, wherein, The liquid hydrocarbon includes at least one of halogenated aromatic hydrocarbons, non-halogenated aromatic hydrocarbons, halogenated aliphatic hydrocarbons, and non-halogenated aliphatic hydrocarbons.

16. The catalyst component according to claim 15, wherein, The liquid hydrocarbon is at least one of benzene and its homologues, chlorobenzene, dichlorobenzene, hexane, heptane, decane, kerosene, dichloromethane, dichloroethane, chloroform, and cyclohexane.

17. The catalyst component according to claim 1, wherein, Based on the amount of magnesium-containing compounds, the organophosphorus compound is 0.01 to 10 moles; the organic epoxy compound is 0.01 to 10 moles; the carbonate compound is 0.001 to 10 moles; the other electron-donating compounds are 0 to 10 moles; and the titanium compound is 0.2 to 100 moles.

18. The catalyst component according to claim 17, wherein, Based on the amount of magnesium-containing compounds, the organophosphorus compound is 0.1 to 4 moles; the organic epoxy compound is 0.1 to 4 moles; the carbonate compound is 0.002 to 1 mole; the other electron-donating compounds are 0 to 4 moles; and the titanium compound is 1.0 to 20 moles.

19. A method for preparing the catalyst component according to any one of claims 1-18, characterized in that, The preparation method includes: (1) The magnesium-containing compound, the organic epoxy compound and the organic phosphorus compound are reacted in the presence of an inert solvent to obtain the magnesium-containing liquid component; (2) The magnesium-containing liquid component obtained in step (1), carbonate compounds, titanium compounds and optional other electron-donating compounds are reacted to produce a precipitate; (3) Remove unreacted substances and solvents, wash the precipitate, and obtain the catalyst component.

20. A catalyst for olefin polymerization, characterized in that, The catalyst comprises the following components: Component A: The catalyst component according to any one of claims 1 to 18; Component B: Organoaluminum compound; its general formula is AlR n X 3-n In the formula, R is a hydrocarbon group with 1 to 20 carbon atoms; X is a halogen; and n is an integer 0 < n ≤ 3.

21. The catalyst according to claim 20, wherein, X is chlorine or bromine.

22. The catalyst according to claim 20, wherein, The molar ratio of aluminum in component B to titanium in component A is 1 to 1000:

1.

23. The catalyst according to claim 22, wherein, The molar ratio of aluminum in component B to titanium in component A is 5 to 500:

1.

24. The catalyst according to claim 20, wherein, The organoaluminum compound is at least one selected from trimethylaluminum, triethylaluminum, triisobutylaluminum, trioctylaluminum, diethylaluminum hydrogen, diisobutylaluminum hydrogen, diethylaluminum chloride, diisobutylaluminum chloride, sesquiethylaluminum chloride, and diethylaluminum chloride.

25. The catalyst according to claim 24, wherein, The organoaluminum compound is triethylaluminum and / or triisobutylaluminum.

26. The use of a catalyst component according to any one of claims 1-18 or a catalyst according to any one of claims 20-25 in an olefin polymerization reaction.

Citation Information

Patent Citations

  • Method for preparing solid titanium catalyst for olefin polymerization

    CN100457788C

  • Catalyst component and catalyst for olefin polymerization, and preparation methods thereof

    CN106478845A

  • Catalyst compositions, catalysts and their preparation methods, composite catalysts, and olefin polymerization methods

    CN112759682B

  • Catalyst active constituent and catalyst containing same

    CN1814627A

  • Catalyst component and catalyst for ethylene polymerization, and preparation method of catalyst component for ethylene polymerization

    CN105384854A